2019
DOI: 10.3892/ijmm.2019.4127
|View full text |Cite
|
Sign up to set email alerts
|

LC‑MS/MS proteomic analysis revealed novel associations of 37 proteins with T2DM and notable upregulation of immunoglobulins

Abstract: Type 2 diabetes mellitus (T2DM) is a disease associated with a number of metabolic disturbances, including protein metabolism. In the present study, blood samples were obtained from Bahraini subjects, including 6 patients with T2DM and 6 age- and sex-matched, non-diabetic, healthy controls. Depleted and non-depleted sera were prepared from the collected blood, and the global protein expression changes were evaluated by liquid chromatography tandem mass spectrometry. Only significantly and markedly differential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 50 publications
1
31
0
Order By: Relevance
“…Mohiuddin et al, [32] that reported hihger level of alpha 1-acid glycoprotein jn type 2 diabetics who were involved in low grade chronic system inflammation that triggered the development of insulin resistance and β cell dysfunction. Abdulawhab et al, [33] reported that enzymatic glycosylation of this protein is involved in future risk of type 2 diabetes. The study is consistent with the report of by Lee et al, [34] that showed elevation level in alpha 1 acid glycoprotein in T2D due to its immunomodulatory in relief of hyperglycaemia, and modulation of immune response to protect adipose tissue from excessive Inflammation and metabolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Mohiuddin et al, [32] that reported hihger level of alpha 1-acid glycoprotein jn type 2 diabetics who were involved in low grade chronic system inflammation that triggered the development of insulin resistance and β cell dysfunction. Abdulawhab et al, [33] reported that enzymatic glycosylation of this protein is involved in future risk of type 2 diabetes. The study is consistent with the report of by Lee et al, [34] that showed elevation level in alpha 1 acid glycoprotein in T2D due to its immunomodulatory in relief of hyperglycaemia, and modulation of immune response to protect adipose tissue from excessive Inflammation and metabolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Protein identi cation: As we reported before [6], the 1-dimensional Nano Acquity liquid chromatography coupled with tandem mass spectrometry on a Synapt G2 instrument (Waters, Manchester, UK) was used for label-free quantitative expression protein pro ling. For ESI Mass Spectrometry analyses, the instrument settings were optimized on the MassLynx tune page.…”
Section: Protein Pro Ling Using Lc-ms/msmentioning
confidence: 99%
“…However, the in uence of the sex hormones in gene expression can't be ignored. Although the human genome is expected to constitute between 20,000 -25,000 genes [5], in our setting proteomic analysis revealed more than 2 millions proteins and peptides (PPs) [6]. A new and expanded central dogma composed of OMICs platforms, including; genome, trasnscriptome and proteome is needed to link the genotypes with the phenotypes.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Sramkova et al (2019) identified apolipoprotein M (apoM) by transcriptome and proteomic analysis of conditioned media from human adipose tissue (AT)-isolated adipocytes and stromal cells, in which the expression level is lower in subjects with metabolic syndrome and T2D and may be associated with insulin sensitivity [32]. Abdulwahab et al (2019) collected sera from healthy people and T2D patients for proteomic mass spectrometry and found that 62 proteins were differentially expressed in T2D, which were functionally grouped into 16 proteins, including heparin cofactor 2, Ig α-1 chain C region, and zinc-α-2-glycoprotein, the largest of which was an immune-related protein [33]. Muralidharan et al (2019) used borate affinity chromatography to isolate glycated erythrocyte proteomes without hemoglobin from controls and DM samples, and proteomic analysis, using the nanoLC/ESI-MS proteomics platform, to identify site-specific glycation of the red blood cell proteome with different glycemic indices in DM patients [34].…”
Section: Human Nutrigenomics and Dmmentioning
confidence: 99%